Dork diaries / Tales from a not-so-talented pop star - Russell, Rachel Renee (DORK diaries, 2010)
New school. New mean girl. New crush. New diary so Nikki can spill all of it... Follow Nikki's life through sketches, doodles and diary entries as she starts her new school, battles with her mum for an iPhone and meets her arch-nemisis, the school's Queen Bee, Mackenzie.